Minutes of the 21st Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
Minutes of the 21st Meeting of BRAC University Academic Council, held on Wednesday, 03 May, 2006.